2014
DOI: 10.1016/j.ijheatmasstransfer.2013.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation of heat transfer enhancement in a channel partially filled with a porous material under local thermal non-equilibrium condition: Effects of different thermal boundary conditions at the porous-fluid interface

Abstract: Mahmoudi, Yasser, Karimi, Nader, and Mazaheri, Kiumars (2014) Analytical investigation of heat transfer enhancement in a channel partially filled with a porous material under local thermal non-equilibrium condition: Effects of different thermal boundary conditions at the porous-fluid interface. International Journal of Heat and Mass Transfer, Copyright © 2013 Elsevier Ltd.A copy can be downloaded for personal non-commercial research or study, without prior permission or charge Content must not be changed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 42 publications
9
64
0
Order By: Relevance
“…(3b) and (3c) are equivalent to model A of Yang and Vafai [31], which has been also used in the investigations of partially filled channels [16,29]. It is emphasised here that previous works [14][15][16] have demonstrated that the choice of porous-fluid boundary condition has significant effects upon the thermal behaviour of the system. In order to make analytical progress with the energy equations (2a) and (2b), their left hand sides should be evaluated.…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3b) and (3c) are equivalent to model A of Yang and Vafai [31], which has been also used in the investigations of partially filled channels [16,29]. It is emphasised here that previous works [14][15][16] have demonstrated that the choice of porous-fluid boundary condition has significant effects upon the thermal behaviour of the system. In order to make analytical progress with the energy equations (2a) and (2b), their left hand sides should be evaluated.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The latter, however, is regarded as local thermal non-equilibrium (LTNE), or two-energy equation model [11,12]. Although LTE model [11] has been used extensively in heat transfer analyses [11], LTNE model is receiving an increasing attention from the research community [13][14][15][16]. This stems from the fact that in the emerging fields such as MEMS and biotechnology as well as some classical areas, such as chemical and nuclear engineering, the accuracy of the analysis is of primary importance [12,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a number of interface models have been developed, some of them are more 38 widely used [40]. Yet, there is no generally preferred porous-fluid or solid interface model and the final choice different interface models to detect the similarities and disparities between their predictions [37,42].…”
mentioning
confidence: 99%
“…[50] for ordinary fluids. Further, in the presence of thermal source terms the temperature fields predicted by the current derivations for φ=0 appear to be identical to those of 1 Ref.…”
mentioning
confidence: 99%